Mothers on the fast track how a new generation can balance family and careers - Mason, Mary Ann.; Ekman, Eve Mason (New York ; Oxford : Oxford University Press, 2007)
This title traces the career paths of the first generation of ambitious women who started careers in academia, law, medicine, business and the media in large numbers in the 1970s and '80s. It is a guide for young women who are facing the tough decision of when - and if - to start a family,also a guide for older women seeking a second chance to break through to the next level.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Working mothers -- United States -- Case studies; Mothers -- Employment -- United States -- Case studies; Work and family -- United States -- Case studies